Comparative Genome and Transcriptome Integration Studies Reveal the Mechanism of Pectoral Muscle Development and Function in Pigeons - Hou, Haobin; Wang, Xiaoliang; Yang, Changsuo; Cai, Xia; Lv, Wenwei; Tu, Yingying; Bao, Aodungerile; Wu, Quanli; Zhao, Weimin; Yao, Junfeng; Ding, Weixing (Frontiers in Genetics, 2021)
Pigeon breed resources provide a genetic model for the study of phenomics. The pectoral muscles are play a key role for the meat production performance of the meat pigeon and the athletic ability of the High flyers. Euro-pigeons and Silver King pigeons are commercial varieties that exhibit good meat production performance. In contrast to the domestication direction of meat pigeons, the traditional Chinese ornamental pigeon breed, High flyers, has a small and light body. Here, we investigate the molecular mechanism of the pectoral muscle development and function of pigeons using whole-genome and RNA sequencing data. The selective sweep analysis (FST and log2 (θπ ratio)) revealed 293 and 403 positive selection genes in Euro-pigeons and Silver King, respectively, of which 65 genes were shared. With the Silver King and Euro-pigeon as the control group, the High flyers were selected for 427 and 566 genes respectively. There were 673 differentially expressed genes in the breast muscle transcriptome between the commercial meat pigeons and ornamental pigeons. Pigeon genome selection signal combined with the breast muscle transcriptome revealed that 6 genes (SLC16A10, S100B, SYNE1, HECW2, CASQ2 and LOC110363470) from commercial varieties of pigeons and 5 genes (INSC, CALCB, ZBTB21, B2M and LOC110356506) from Chinese traditional ornamental pigeons were positively selected which were involved in pathways related to muscle development and function. This study provides new insights into the selection of different directions and the genetic mechanism related to muscle development in pigeons.